Porosity of temporary denture soft liners containing antifungal agents - Mello Lima, Jozely Francisca; Maciel, Janaina Gomes; Hotta, Juliana; Pero Vizoto, Ana Carolina [UNESP]; Honorio, Heitor Marques; Urban, Vanessa Migliorini; Neppelenbroek, Karin Hermana (Univ Sao Paulo Fac Odontologia Bauru, 2016)
Incorporation of antifungals in temporary denture soft liners has been recommended for denture stomatitis treatment; however, it may affect their properties. Objective: To evaluate the porosity of a tissue conditioner (Softone) and a temporary resilient liner (Trusoft) modified by minimum inhibitory concentrations (MICs) of antifungal agents for Candida albicans biofilm. Material and Methods: The porosity was measured by water absorption, based on exclusion of the plasticizer effect. Initially, it was determined by sorption isotherms that the adequate storage solution for specimens (65x10x3.3 mm) of both materials was 50% anhydrous calcium chloride (S50). Then, the porosity factor (PF) was calculated for the study groups (n=10) formed by specimens without (control) or with drug incorporation at MICs (nystatin:Ny-0.032 g, chlorhexidine diacetate: Chx-0.064 g, or ketoconazole: Ke-0.128 g each per gram of soft liner powder) after storage in distilled water or S50 for 24 h, seven and 14 d. Data were statistically analyzed by 4-way repeated measures ANOVA and Tukey's test (alpha=.05). Results: Ke resulted in no significant changes in PF for both liners in water over 14 days (p>0.05). Compared with the controls, Softone and Trusoft PFs were increased at 14-day water immersion only after addition of Ny and Chx, and Chx, respectively (p<0.05). Both materials showed no significant changes in PF in up to 14 days of S50 immersion, compared with the controls (p>0.05). In all experimental conditions, Softone and Trusoft PFs were significantly lower when immersed in S50 compared with distilled water (p<0.05). Conclusions: The addition of antifungals at MICs resulted in no harmful effects for the porosity of both temporary soft liners in different periods of water immersion, except for Chx and Ny in Softone and Chx in Trusoft at 14 days. No deleterious effect was observed for the porosity of both soft liners modified by the drugs at MICs over 14 days of S50 immersion.
Keywords: Denture stomatitis; Denture liners; Porosity; Anti-infective agents